Perancangan Ulang Tata Letak Fasilitas Produksi dengan Metode from to Chart pada Perusahaan Meubel di CV. Esa Banyuwangi - Yustian Suhandinata (Fakultas Teknik Universitas Cenderawasih, 2023)
Layout is one of the strategic operational decisions that also determines the efficiency of the company's operations in the long term. The right layout shows the characteristics of the adjustment of the layout of the operational facilities with the products or types of services produced and their conversion processes. A good layout will contribute to increasing the company's productivity. CV. ESA is a furniture company that produces multi-products with a make-to-order production system. The layout of the production department at CV. ESA has problems in terms of the distance of moving the cutting results to the installation of the frame which is less efficient. The purpose of the study is to find out and redesign a good production facility layout so that it can minimize the distance and cost of material handling at CV. ESA Banyuwangi. The results of the redesign of the production facility layout concluded that the effective and efficient arrangement of the department layout is in the sequence B C I J K M N O. From the results of data processing, it was obtained about the redesign of the production facility layout in order to obtain a comfortable work area and to minimize the distance of material movement with a total distance of movement per day of 2,516 smaller than the initial layout of 4,916. Calculation of optimum material transfer costs for the initial layout Material transfer costs per month = Rp 23,990 while in the proposed layout Material transfer costs per month = Rp 12,239.